ANALISIS TINGKAT KEPUASAN PASIEN ATAS KUALITAS PELAYANAN JASA KESEHATAN PADA PUSKESMAS PAYUNG SEKAKI KOTA PEKANBARU - Ufi Mitsaqy; Jushermi Jushermi; Henni Noviasari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The aim of this research is to determine the level of patient satisfaction over the quality of health services at Payung Sekaki clinic in Pekanbaru. The population of the research are patient who seeks treatment at Payung Sekaki Clinic Pekanbaru in 2014, total of 32.272 people. While the sample of this research provides the sample of 100 people by using accidental sampling technique. In conducting this research, Importance Performances Analysis (IPA) was used as the Analysis of the data. The Results of the research with an average of respondents answers to the level of satisfaction was 76.84 Tangible variables was included in the category are satisfied. Then the respondents level of satisfaction was 76.26 Emphaty variables are included in the category are satisfied. Furthermore, variable patient satisfaction is Reliability with 67.97 satisfied category. Then, The level of patient satisfaction with the variables 67.29 Responsiveness is satisfied category, while the lowest value variabel with 66.58, contained as the complaint handling system responsive. The total average level of satisfaction was 68.62 patient with Assurance variable satisfied category means a comparison between expectations and performance are in accordance with the commits of the patient. From the results and discussion, it was discovered that the health center Payung Sekaki Clinic in Pekanbaru city has been satisfactory for health center patients.Keywords: Service Quality, Satisfaction